Strengthening routine immunization in Papua New Guinea: a cross-sectional provincial assessment of front-line services - Christopher J. Morgan; Olga P. M. Saweri; Nicholas Larme; Elizabeth Peach; Pele Melepia; Lucy Au; Michelle J. L. Scoullar; Mohammad Salim Reza; Lisa M. Vallely; Barbara I. McPake; James G. Beeson (BMC, 2020)
Abstract Background Routine immunization programs face many challenges in settings such as Papua New Guinea with dispersed rural populations, rugged geography and limited resources for transport and health. Low routine coverage contributes to disease outbreaks such as measles and the polio that re-appeared in 2018. We report on an in-depth local assessment that aimed to document immunization service provision so as to review a new national strategy, and consider how routine immunization could be better strengthened. Methods In East New Britain Province, over 2016 and 17, we carried out a cross-sectional assessment of 12 rural health facilities, staff and clients. The study was timed to follow implementation of a new national strategy for strengthening routine immunization. We used interview, structured observation, and records review, informed by theory-based evaluation, a World Health Organization quality checklist, and other health services research tools. Results We documented strengths and weaknesses across six categories of program performance relevant to national immunization strategy and global standards. We found an immunization service with an operational level of staff, equipment and procedures in place; but one that could reach only half to two thirds of its target population. Stronger routine services require improvement in: understanding of population catchments, tracking the unvaccinated, reach and efficiency of outreach visits, staff knowledge of vaccination at birth and beyond the first year of life, handling of multi-dose vials, and engagement of community members. Many local suggestions to enhance national plans, included more reliable on-demand services, integration of other family health services and increased involvement of men. Conclusions The national strategy addresses most local gaps, but implementation and resourcing requires greater commitment. Long-term strengthening requires a major increase in centrally-allocated resources, however there are immediate locally feasible steps within current resources that could boost coverage and quality of routine immunization especially through better population-based local planning, and stronger community engagement. Our results also suggest areas where vaccination campaigns in PNG can contribute to routine immunization services.